INOCERAMID/FORAMINIFERAL SUCCESSION OF THE TURONIAN AND CONIACIAN (UPPER CRETACEOUS) OF THE BRIANSK REGION (CENTRAL EUROPEAN RUSSIA) - Walaszczyk I.; Kopaevich L.F.; Olferiev A.G. (My University, 2004)
An integrated inoceramid-foraminiferal zonation for the topmost Turonian and Lower Coniacian near Briansk, SW of Moscow is presented. The inoceramid fauna enables the application of the refined zonal scheme currently applied in central and western Europe. Three zones based on benthic foraminifera, the Gavelinella moniliformis, Ataxophragmium nautiloides and Stensioeina granulata granulata zones; and three zones based on planktonic foraminifera, the Whiteinella archaeocretacea, Marginotruncana pseudolinneiana and Marginotruncana renzi zones, are distinguished. The Turonian/ Coniacian boundary, defined by the first appearance of the inoceramid Cremnoceramus deformis erectus (MEEK, 1877), falls within the basal part of the Stensioeina granulata granulata Zone and the basal part of Marginotruncana renzi Zone. In foraminiferal terms the Turonian/Coniacian boundary interval is marked additionally by a sudden, short-lived increase in the plankton/benthos ratio, caused primarily by more abundant shallow-water morphotypes.
Keywords: Coniacian; Turonian; Mesozoic::Cretaceous::Upper::Coniacian; Мезозой::Меловая::Верхний::Коньякский; Mesozoic::Cretaceous::Upper::Turonian; Мезозой::Меловая::Верхний::Туронский